Philosophy and Theological Discourse
XIV, 232 p.
Keywords: This book represents conversations between philosophers and theologians on several issues of current theological interest. God, the church, theological authority, atonement, the Holy Spirit, religious ethics, the problem of evil, and other topics are debated by top-notch theologians and philosophers of various theological and philosophical persuasions. Since contemporary philosophers and theologians seldom communicate professionally, this book represents a fascinating and highly unusual cross-disciplinary conversation.